2000
DOI: 10.1176/appi.ps.51.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Use of Community Support Services by Middle-Aged and Older Patients With Psychotic Disorders

Abstract: Use of community services is common among older outpatients with psychotic disorders, but its frequency varies as a function of patient characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Similar to the findings of Shaw et al (2000), high users of formal community support services (e.g. social services, daily living services and psychological services), in the present study, were more depressed.…”
Section: Impact Of Health/social Service Use On Trajectories Of Depresupporting
confidence: 89%
“…Similar to the findings of Shaw et al (2000), high users of formal community support services (e.g. social services, daily living services and psychological services), in the present study, were more depressed.…”
Section: Impact Of Health/social Service Use On Trajectories Of Depresupporting
confidence: 89%
“…It has been suggested that utilisation of services is predicted more by functional status rather than severity of psychotic symptoms. Shaw, Patterson & Semple (2000) found that elderly patients with schizophrenia residing in the community utilised services to a level comparable to community patients with AD. McNulty et al (2003) have raised concerns about the serious shortcomings in the standards of hospital and community care for elderly patients with schizophrenia and have identified low spending, shortage of consultants and uncertainty about responsibility of care as reasons for this problem.…”
Section: Psychiatric Service Needsmentioning
confidence: 95%
“…In their study of older persons with psychotic disorders, Shaw et al (2000) found that over 90% used psychological services and daily living services and over 50% used some type of social service at least once within the past 6 months. Another study of older adults with bipolar disorder and major depression found that such clients used case management services, partial hospitalization programs, psychiatric medication checks, and group therapy programs (Bartels, Forester, Miles, & Joyce, 2000).…”
Section: Sources Of Assistance For the Older Smi Populationmentioning
confidence: 99%